Prediction of Compressor Blade Erosion Experiments in a Cascade Based on Flat Plate Specimen - Lorenz, Max; Klein, Markus; Hartmann, Jan; Koch, Christian; Staudacher, Stephan (Frontiers in Mechanical Engineering, 2022)
Erosion is an essential deterioration mechanism in compressors of jet engines. Erosion damage predictions require the determination of erosion rates through flat plate experiments. The applicability of the erosion rates is limited to conditions which are comparable to the prevailing boundary conditions of the flat plate experiment. A performed dimensional analysis enables the correct transfer of the flat plate erosion rates to the presented physical calculation model through limits in spatial and time resolution. This efficient approach avoids computationally intensive single-impact computations. The approach features a re-meshing procedure which adheres to the limits derived by the dimensional analysis. The computation approach is capable of describing local geometry changes on cascade compressor blades which are exposed to erosive particles. A linear erosion cascade experiment performed for NASA Rotor 37 provides validation data for the calculated erosion-induced shape change. Arizona Road Dust particles are used to deteriorate Ti-Al6-4V compressor blades. The experiment is performed at an incidence of i=7° and Ma = 0.76 representing ground idle conditions. The presented parametric study for element size and time step revealed preferable values for the presented computation. Calculations performed with the determined values showed that the erosion prediction is within the measurement tolerance of the experiment and therefore high accordance between the computation and the experiment is achieved. To extend the current state of the art, it is demonstrated that the derived discretization is decisive for the correct reproduction of the eroded geometries and fitting parameters are no longer needed. The good agreement between the experimental measurements and the calculated results confirm the correct application of the physical model to the phenomenology of erosion. Thus, the presented physical model offers a novel approach to adapt deterioration mechanisms caused by erosion to any compressor blade geometry.